Liraglutide Alleviates Hepatic Steatosis by Activating the TFEB-Regulated Autophagy-Lysosomal Pathway - Fang, Yunyun; Ji, Linlin; Zhu, Chaoyu; Xiao, Yuanyuan; Zhang, Jingjing; Lu, Junxi; Yin, Jun; Wei, Li (Frontiers in Cell and Developmental Biology, 2020)
Liraglutide, a glucagon-like peptide-1 receptor agonist (GLP-1RA), has been demonstrated to alleviate non-alcoholic fatty liver disease (NAFLD). However, the underlying mechanism has not been fully elucidated. Increasing evidence suggests that autophagy is involved in the pathogenesis of hepatic steatosis. In this study, we examined whether liraglutide could alleviate hepatic steatosis through autophagy-dependent lipid degradation and investigated the underlying mechanisms. Herein, the effects of liraglutide on NAFLD were evaluated in a high-fat diet (HFD)-induced mouse model of NAFLD as well as in mouse primary and HepG2 hepatocytes exposed to palmitic acid (PA). The expression of the GLP-1 receptor (GLP-1R) was measured in vivo and in vitro. Oil red O staining was performed to detect lipid accumulation in hepatocytes. Electron microscopy was used to observe the morphology of autophagic vesicles and autolysosomes. Autophagic flux activity was measured by infecting HepG2 cells with mRFP-GFP-LC3 adenovirus. The roles of GLP-1R and transcription factor EB (TFEB) in autophagy-lysosomal activation were explored using small interfering RNA. Liraglutide treatment alleviated hepatic steatosis in vivo and in vitro. In models of hepatic steatosis, microtubule-associated protein 1B light chain-3-II (LC3-II) and SQSTM1/P62 levels were elevated in parallel to blockade of autophagic flux. Liraglutide treatment restored autophagic activity by improving lysosomal function. Furthermore, treatment with autophagy inhibitor chloroquine weakened liraglutide-induced autophagy activation and lipid degradation. TFEB has been identified as a key regulator of lysosome biogenesis and autophagy. The protein levels of nuclear TFEB and its downstream targets CTSB and LAMP1 were decreased in hepatocytes treated with PA, and these decreases were reversed by liraglutide treatment. Knockdown of TFEB expression compromised the effects of liraglutide on lysosome biogenesis and hepatic lipid accumulation. Mechanistically, GLP-1R expression was decreased in HFD mouse livers as well as PA-stimulated hepatocytes, and liraglutide treatment reversed the downregulation of GLP-1R expression in vivo and in vitro. Moreover, GLP-1R inhibition could mimic the effect of the TFEB downregulation-mediated decrease in lysosome biogenesis. Thus, our findings suggest that liraglutide attenuated hepatic steatosis via restoring autophagic flux, specifically the GLP-1R-TFEB-mediated autophagy-lysosomal pathway.